Effect of switching to teneligliptin from other dipeptidyl peptidase‐4 inhibitors on glucose control and renoprotection in type 2 diabetes patients with diabetic kidney disease. Issue 3 (1st October 2018) - Kitada, Munehiro; Ogura, Yoshio; Nitta, Kyoko; Fujii, Mizue; Kanasaki, Keizo; Konishi, Kazunori; Iida, Yasuo; Nakagawa, Atsushi; Koya, Daisuke
Abstract: Aims/Introduction: The objective of the present study was to elucidate the effect of switching to teneligliptin from other dipeptidyl peptidase‐4 (DPP‐4) inhibitors on glucose control and renoprotection in type 2 diabetes mellitus patients with diabetic kidney disease. Materials and Methods: The present study was a single‐arm, open‐label, observational study. A total of 23 patients, who had urinary albumin/creatinine ratios (UACR) ≥30 mg/gCr in their first urine in the early morning, and received other DPP‐4 inhibitors and renin‐angiotensin system inhibitors, switched to teneligliptin 20 mg/day. After switching to teneligliptin for 24 weeks, we evaluated changes in glycated hemoglobin (HbA1c), fasting plasma glucose levels, plasma DPP‐4 activity and UACR. Results: HbA1c, fasting plasma glucose and UACR values showed no significant change after 24 weeks compared with baseline. However, plasma DPP‐4 activity was significantly reduced after 24 weeks (0.57 ± 0.26 nmol/min/mL, P = 0.012, vs baseline), compared with baseline (1.49 ± 1.73 nmol/min/mL), and there was a positive relationship between the change rate of plasma DPP‐4 activity (Δ%DPP‐4) for 24 weeks and the levels of plasma DPP‐4 activity ( r = −0.5997, P = 0.0025) and fasting plasma glucose ( r = −0.4235, P = 0.0440) at baseline. Additionally, the Δ%DPP‐4 for 24 weeks was significantly correlated to the change rate of UACR ( r = 0.556, P = 0.0059). However, there was no relationship between Δ%DPP‐4 and ΔHbA1c (amount of HbA1c change). Conclusions: Switching to teneligliptin from other DPP‐4 inhibitors for 24 weeks reduces plasma DPP‐4 activity, which is associated with a reduction in albuminuria, independent of the change in glucose levels, in type 2 diabetes mellitus patients with diabetic kidney disease. Abstract : Switching to teneligliptin from other DPP‐4 inhibitors for 24 weeks leads to a decrease in plasma DPP‐4 activity in type 2 diabetes mellitus patients with DKD. Reduction of plasma DPP‐4 activity is closely related to a reduction in the urinary albumin/creatinine ratio, independently of the glucose‐lowering effect.